The chain-mediating role of caregiver burden and illness uncertainty between social support and preparedness among family caregivers of spinal cord injury patients - Shuyuan Zhuang; Jiao Wu; Delong Li; Li Li; Sihong Dong; Yuantong Zang (PLoS ONE, 2026)
Objective This study aimed to examine the effects of social support, caregiver burden, and illness uncertainty on preparedness among family caregivers of individuals with spinal cord injury (SCI), and to analyze the mediating roles of caregiver burden and illness uncertainty in the relationship between social support and preparedness. Methods A cross-sectional survey was conducted between June 2024 and April 2025 among conveniently selected SCI patients and their family caregivers from the orthopedics departments of two tertiary hospitals in Hohhot, China. Data were collected using the General Information Questionnaire, the Mishel Uncertainty in Illness Scale, the Social Support Rating Scale, the Chinese version of the Caregiver Burden Inventory, and the Chinese version of the Preparedness for Caregiving Scale. Results Correlation analyses indicated that caregivers’ preparedness was positively correlated with social support and negatively correlated with caregiver burden and illness uncertainty. Mediation analyses revealed that social support not only directly enhanced preparedness but also indirectly improved it by alleviating caregiver burden and reducing illness uncertainty. Furthermore, caregiver burden and illness uncertainty were found to form a sequential mediation pathway between social support and preparedness. Conclusion Social support enhances preparedness both directly and indirectly through reducing caregiver burden and illness uncertainty. To translate these findings into practice, healthcare providers should routinely assess caregivers’ support needs, integrate burden screening into follow-up visits, and offer uncertainty-management counseling. Hospital- and community-based support programs focusing on skill-building and peer support are also recommended to strengthen caregiver preparedness.